PENDEKATAN SAINTIFIK MODEL DISCOVERY LEARNING DAN METODE DISKUSI KELOMPOK UNTUK MENINGKATKAN AKTIFITAS DAN HASIL BELAJAR PPKN DI KELAS VII 3 MTsN 1 PAYAKUMBUH - Afni Wira Yulia; Yenti Murni; Shaif Abdul Hadi (Kampus Akademik Publiser, 2023)
Abstract. The background of this research is to see and analyze the improvement in student learning outcomes in PPKN subjects, the subject of forms of cooperation in various areas of life in society through a scientific approach, discovery learning model, group discussion method in Class VII.3 MTsN 1 Payakumbuh. This research uses the Classroom Action Research method which consists of two cycles, where each cycle consists of; planning, action, observation and reflection. Data is processed in each cycle and then analyzed using percentages. The results of research using a scientific approach, the Discovery Learning model, the group discussion method, can improve students' activities and learning outcomes. This is evident from the increase in student learning activities in the pre-cycle which was 36%, in the first cycle 55% and in the second cycle 83%. For pre-cycle teacher activities it was 55%, for cycle I 75% and increased in cycle II to 91%. for learning completeness, knowledge increased from pre-cycle 72.82=41%, cycle I 76.15=72%, and cycle II 85.89=82%. For skill learning completeness, namely pre-cycle 70.77=44%, cycle I 71.54=54%, and cycle II 80.64=85%. Conclusion: By using the scientific approach to the Discovery Learning model, the group discussion method can improve student learning outcomes.